A new algorithm of preoperative preparation of patients with focal lesions of the biliopancreatic area complicated by mechanical jaundice - Рetro Мuraviov; Boris Zaporozhchenko; Igor Borodaev; Valeria Shevcheko; Makrem Harhouri (Kazimierz Wielki University, 2021)
Pancreatoduodenal resection (PDR) represents one of the most demanding procedures which is required in patients with a tumoral lesion at this level. The aim of the present article was to report the results of 272 patients submitted to such surgical procedures. All patients were divided into two groups: the main group, for whom the optimized decompression algorithm was used (n=112) and the control group, for whom preparation for PDR was carried out according to generally accepted standards (n=160). Upon admission to the hospital, the total bilirubin level in the main group was 274.6±5.9 µmol/l while in the control group this level was 270.4±4.6 µmol/l. PDR was performed in 272 of the patients. Whipple's terminolateral anastomosis was performed in 38/160 (23.7%) of patients in the control group; termino-terminal anastomosis according to Shalimov-Kopchak's method was imposed in 40/160 (25.0%) patients of the control group. Pancreatojejunoanastomosis with the imposition of a ductomucosal anastomosis was performed in 128 patients in total with 73 cases in the main group and in 55 cases in the control one. Pancreatogastroanastomosis with plunging of the pancreatic stump into the stomach stump was performed in 35 patients in total with 19 patients in the main group and 16 in the control group. Pancreatogastroanastomosis with plunging of the pancreatic stump into the 'stomach sleeve' was performed in 32 patients in total with 20 patients in the main group and 12 in the control group. The mortality rate in the main group was 6.3% (7 patients), and in the control group, 11.9% (19 patients). In conclusion, biliary decompression may improve the postoperative outcomes after pancreatic resection. Abbreviations: CEA, carcinoembryonic antigen; CA, cancer antigen; PDR, pancreatoduodenal resection; MRI, magnetic resonance imaging